2015
DOI: 10.1080/15222055.2015.1090505
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Age‐0 Hatchery Summer‐Run Chinook Salmon is Enhanced by Early Release

Abstract: Subyearling (age-0) hatchery summer-run Chinook Salmon Oncorhynchus tshawytscha have been released into the Columbia River in mid-June from Wells Fish Hatchery, Washington, since 1993, but release-to-adult survival (SAR) under this strategy has been low. I used paired releases of four broods of coded-wiretagged age-0 Chinook Salmon released in mid-May (early release [ER] group) and mid-June (late release [LR] group) to evaluate whether advancing the release date could improve SAR. Additionally, passive integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…Our multi-hatchery model results found that survival rates are expected to increase for releases of sub-yearling Chinook salmon from early May to early-June, yearling Chinook salmon from mid-April to early May, and yearling coho salmon from mid-May to mid-June, which is consistent with other studies (Mathews and Ishida 1989;Duffy and Beauchamp 2011;Snow 2016). Sub-yearling or "ocean-type" Chinook salmon are the most common life history in BC, generally entering the marine environment within 3 months after emergence from the gravel (i.e., less than 1-year of freshwater residency) and returning to spawn in between August and October (Groot and Margolis 1991).…”
Section: Coho Yearling Smoltssupporting
confidence: 91%
“…Our multi-hatchery model results found that survival rates are expected to increase for releases of sub-yearling Chinook salmon from early May to early-June, yearling Chinook salmon from mid-April to early May, and yearling coho salmon from mid-May to mid-June, which is consistent with other studies (Mathews and Ishida 1989;Duffy and Beauchamp 2011;Snow 2016). Sub-yearling or "ocean-type" Chinook salmon are the most common life history in BC, generally entering the marine environment within 3 months after emergence from the gravel (i.e., less than 1-year of freshwater residency) and returning to spawn in between August and October (Groot and Margolis 1991).…”
Section: Coho Yearling Smoltssupporting
confidence: 91%